The 1935 Dominion Housing Act: Setting the Stage for a Permanent Federal Presence in Canada's Housing Sector - Hulchanski, J. (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1986)
In the midst of the social, economic and political turmoil of the 1930s a range of federal housing policy and program options were debated. After appointing a special housing committee of the House of Commons in February 1935, and then ignoring all its recommendations, the R.B. Bennett government adopted the Dominion Housing Act (DHA) in June 1935. This paper examines the development and implementation of the DHA and finds that the legislation was of little consequence to the housing sector and that it provided no benefits to lower income households. However, in terms of a long term precedent for defining an "appropriate" role for government in Canada's housing sector, the DHA is very significant. The key actors in designing the DHA, Deputy Finance Minister W.C Clark and the mortgage lending companies, including Sun Life's David B. Mansur, played a central role in defining housing policy into the early 1950s. Together they successfully protected the status quo from alternative policy options. Starting with the DHA, Canadian housing policy has, as a result, a long history of focusing more on "market welfare" than on "social welfare" approaches to housing problems.